Exploring how values are embedded in technology, and its influence on society : a study of the post-school education and training sector in South Africa - Myburgh, Suzanne (University of Pretoria, 2025)
Mini Dissertation (MPhil (Corporate Strategy))--University of Pretoria, 2024.